Pengaruh Firm Size, Audit Fee dan Leverage Terhadap Integritas Laporan Keuangan: (Studi Pada Perusahaan Infrastruktur yang Terdaftar di BEI Pada Tahun 2021-2023) - Indrawan, Andri; Himawan, Irfan Sophan; Gusmarani, Zesika; Rahmadini, Salma Amelia; Aulia Rahmadini, Salva (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2023)
This study aims to analyze and explain the influence of firm size, audit fees, and leverage on financial statement integrity, both partially and simultaneously, in infrastructure companies listed on the Indonesia Stock Exchange for the 2021–2023 period. The background of this study is based on the importance of financial statement integrity in reflecting actual financial conditions and supporting reliable decision-making. The research method used is a quantitative approach with multiple linear regression analysis techniques using IBM SPSS version 30 software on a sample of 66 companies (22 companies multiplied by 3 years of research). The results show that partially, firm size has a negative and significant effect on financial statement integrity, meaning that the larger the company size, the level of financial statement integrity tends to decrease. Meanwhile, audit fees and leverage do not have a significant effect on financial statement integrity. Simultaneously, these three variables have a significant effect on financial statement integrity with a coefficient of determination of 20.9%, while the remaining 79.1% is influenced by other factors such as good corporate governance, audit tenure, and earnings management. These findings are expected to serve as a reference in efforts to improve transparency and accountability in financial reporting.